Towards evidence-based dosing regimens in children on the basis of population pharmacokinetic pharmacodynamic modelling. Issue 3 (19th December 2013) - Admiraal, Rick; van Kesteren, Charlotte; Boelens, Jaap Jan; Bredius, Robbert G M; Tibboel, Dick; Knibbe, Catherijne A J
Abstract : When growing up, the pharmacokinetic (PK) and pharmacodynamic (PD) profiles of drugs change, which may alter the effect of drugs. To ensure optimal drug efficacy and safety in paediatric care, PK and PD relationships of drugs need to be explored in children. This article presents an outline on performing a population PK/PD study and translating these results into rational dosing regimens, with the development and prospective evaluation of PK/PD derived evidence-based dosing regimen being discussed. Examples on amikacin, morphine and busulfan are provided, showing how PK(/PD) modelling not only led to optimization and individualization in paediatric clinical care for the specific drugs but also to insight in maturation of organ systems involved. It is shown that the latter results can subsequently be used as a basis for dosing of other drugs eliminated through the same pathway. Ultimately, these efforts should lead to predictable drug efficacy and safety across all age groups.